Tracking Acquired Antibiotic Resistance in Commensal Bacteria of Galápagos Land Iguanas: No Man, No Resistance - Thaller, Maria Cristina; Migliore, Luciana; Marquez, Cruz; Tapia, Washington; Cedeño, Virna; Rossolini, Gian Maria; Gentile, Gabriele (PLOS ONE, 2010)
Background Antibiotic resistance, evolving and spreading among bacterial pathogens, poses a serious threat to human health. Antibiotic use for clinical, veterinary and agricultural practices provides the major selective pressure for emergence and persistence of acquired resistance determinants. However, resistance has also been found in the absence of antibiotic exposure, such as in bacteria from wildlife, raising a question about the mechanisms of emergence and persistence of resistant strains under similar conditions, and the implications for resistance control strategies. Since previous studies yielded some contrasting results, possibly due to differences in the ecological landscapes of the studied wildlife, we further investigated this issue in wildlife from a remote setting of the Galapagos archipelago. Methodology/Principal Findings Screening for acquired antibiotic resistance was carried out in commensal enterobacteria from Conolophus pallidus, the terrestrial iguana of Isla Santa Fe, where: i) the abiotic conditions ensure to microbes good survival possibilities in the environment; ii) the animal density and their habits favour microbial circulation between individuals; and iii) there is no history of antibiotic exposure and the impact of humans and introduced animal species is minimal except for restricted areas. Results revealed that acquired antibiotic resistance traits were exceedingly rare among bacteria, occurring only as non-dominant strains from an area of minor human impact. Conclusions/Significance Where both the exposure to antibiotics and the anthropic pressure are minimal, acquired antibiotic resistance traits are not normally found in bacteria from wildlife, even if the ecological landscape is highly favourable to bacterial circulation among animals. Monitoring antibiotic resistance in wildlife from remote areas could also be a useful tool to evaluate the impact of anthropic pressure.